Presentation - Rodríguez Chávez, Iván (2020)
In this year 2020, painful, devastating and unfortunate due to the atrocious consequences of the pandemic caused by the COVID-19, we commemorate one hundred years of this nefarious event. For this reason, the Ricardo Palma University, the Editorial Fund of the Judiciary, the Vice-Deanship of Research and Graduate Studies of the Faculty of Letters and Human Sciences of the Universidad Nacional Mayor de San Marcos, the Institute of Vallejo Studies of the National University of Trujillo, the Center for Vallejo Studies, and Capulí, Vallejo y su Tierra organized the colloquium "Centennial of the judicial process followed against the poet César Vallejo", developed virtually on Saturdays November 7, 14, 21 and 28.